Corporate Liability for Conducting Mining Activities in Forest Areas Without Ministerial Permission Under the Environmental Protection and Management Law - Salin, Salin; Syaufi, Ahmad; Ifrani, Ifrani; Saprudin, Saprudin (Scholar Center, 2024)
The responsibility of corporations engaged in mining activities within forest areas without the Minister's permit is an important issue in the context of environmental protection and management in Indonesia. Law No. 32 of 2009 on Environmental Protection and Management (UUPPLH) regulates the obligation of all parties, including corporations, to conduct business activities while considering environmental sustainability. In this case, corporations that engage in mining activities without the Minister's permit are considered to violate existing regulations, which may lead to both criminal and administrative sanctions. This study aims to examine the extent of corporate responsibility for environmental damage caused, as well as the implications for law enforcement and environmental protection. The research uses a normative legal method with a legislative, conceptual, and comparative approach, focusing on the analysis of Article 89 Paragraph (2) letter (a) of the P3H Law and its implementation in the enforcement of law related to corporate crimes in the mining sector. Furthermore, the study will discuss how existing policies and regulations can improve corporate accountability in carrying out environmentally friendly mining activities. Through this analysis, it can be concluded that Article 89 Paragraph (2) letter (a) of the P3H Law does not clearly specify who is responsible, preventing the corporate management from being held criminally accountable. This undermines the purpose of the law to provide certainty, justice, and benefits. As a result, the law fails to achieve its goals of criminal punishment and legal protection for the welfare of society and environmental preservation.